Symbolic irruption in the Mapuche social movement. An overview of its audiovisual production - Pereira Covarrubias, Andrés (2016)
This paper focuses on the audiovisual productions of Gulumapu Mapuche (the Mapuche territory located in Chile), developed since the late twentieth century in the context of indigenous processes of socioterritorial resistance and struggle emerged in Chile during the period of postdictatorial transition; in relation to a wider context of socio-environmental conflicts, due to the advancement of extractive economic model in the region. Through tools of documentary film theory and cinema aesthetics, a general description of these film works is displayed, identifying the predominant mode of representation and the discourses interweaving these processes.